The Relationship Between Emotional Maturity and Coping Efficacy Mediated by Authoritative Parenting Styles In Adolescents - Nur Fawaid, Mohammad Habib (Devotion : Journal of Research and Community Service, 2026)
This study aims to examine the relationship between emotional maturity and coping efficacy with authoritative parenting style as a mediating variable among late adolescents. Using a quantitative correlational design, the research involved 15–17-year-old students selected through purposive sampling. Data were collected using the Emotional Maturity Scale (EMS), Coping Efficacy Questionnaire (CEQ-17), and Parental Authority Questionnaire (PAQ). The data analysis was performed using mediation analysis with PROCESS Hayes version 2.14. The results showed a significant direct relationship between emotional maturity and coping efficacy, as well as between authoritative parenting style and coping efficacy. However, emotional maturity did not significantly predict authoritative parenting style. Furthermore, the mediation analysis revealed that the authoritative parenting style did not serve as a mediator between emotional maturity and coping efficacy. These findings suggest that while emotional maturity and authoritative parenting independently contribute to adolescents’ coping efficacy, authoritative parenting does not function as a mediating mechanism in this relationship. Future studies are recommended to include demographic and parenting-related variables for deeper analysis.